Development of the elite athlete - Bennett, D. (FILA Advanced school for coaches - proceedings 2013, 2013)
When one starts to discuss a topic such as the "Development of the Elite Athlete" it is important to keep in mind the fact that in a room full of coaches who have spent their career working with Elite Athletes, a simple singular uniform approach would be very difficult to settle upon. This is due in part to the fact that the path to success has not been the same for all and that there are many cultural differences that come into play. There is a strong tendency of coaches to follow in the footsteps of their own personal coach or coaches and draw heavily upon their own experience as a athlete. A philosophy of "this is the way I was taught, this is the way I did it, and it worked for me." This is human nature and certainly has some merit if in fact, there is a history of proven success behind it. So while not in all areas, at least in some, I think it is safe to say that we can agree that coaches will disagree on means and methods of the development of young athletes. I personally believe this is a good thing and that healthy discussion with an open mind on topics such as this results in building a better foundation for working with talented young athletes. Remember the mind is like a parachute, it doesn`t do you any good if it doesn`t open.